Sociodemographic factors: the interference in patients in the period after making intestinal ostomies (Research, Society and Development, 2022)
Objective: to list the main factors, internal and external, that interfere in the hospital readmission process of ostomy patients. Methodology: quantitative and qualitative, descriptive and field study. A questionnaire was applied online to 23 participants who underwent an intestinal ostomy at a Teaching Hospital in Minas Gerais, Brazil. Patients who underwent intestinal ostomy in the period from 2015 to 2019 met the inclusion criteria. Patients who refused to participate in the research and/or who did not have telephone contact were excluded. Data were generated in Excel® software and descriptive and thematic content analysis was performed. Results: there was a predominance of females 14 (60.9%), aged over 50 years 13 (56.5%), with complete primary education 7 (30.4%), 11 (47.8%) with income between one and two minimum wages, most 17 (73.9%) have access to the Health Unit. It was also noticed, in the majority (43.47%), of the patients the negative feeling about self-care with the ostomy. Conclusion - the main factors that interfere in the hospital readmission process are the low level of education and income, considering that these are factors that hinder access to information, a fundamental factor for proper care with the ostomy.